The Unyielding Current: Migration And Its Transformative Impact On Service Provision In Nepalgunj Sub-Metropolitan City (Voice: A Biannual & Bilingual Journal, 2025)
This paper reports on an in-depth study of how migration issues are addressed in urban service delivery in Nepalgunj Sub-Metropolitan City (Nepalgunj-S). Situated on the India-Nepal border and the East-West Highway, Nepalgunj functions as a critical magnet for diverse migration streams, including internal Displacement from surrounding hill districts (e.g., Jajarkot, Rolpa, Surkhet, Dailekh), cross-border flows for labour, trade, and healthcare from neighbouring Indian districts (e.g., Bahraich, Gonda), return migration from Gulf countries and Malaysia, and Displacement due to environmental hazards like riverine flooding. The analysis highlights how rapid and continuous migration increases the strain on vital services, including water, sanitation, healthcare, education, housing, waste management, and transportation, by combining secondary data from academic literature, census records, and local reports. Key findings highlight critical strains, including overburdened water supplies and sanitation exclusion in informal settlements, overwhelmed public healthcare facilities compounded by medical tourism, overcrowded public schools alongside rising private sector demand, proliferating informal housing lacking tenure security, rampant illegal dumping and inadequate waste processing, and severe traffic congestion. The study concludes that conventional governance and planning approaches are insufficient. It makes a case for an inclusive, adaptive, and proactive urban governance that is firmly committed to the idea of migration and explicitly acknowledges it as the primary force that characterizes Nepalgunj’s present and future, thus underscoring the need for integrated planning, fiscal innovation, and targeted infrastructure investment to build resilience and equity.